BITE: Recipes for Remarkable Research - Williams, Alison; Jones, Derek; Robertson, Judy (Brill, 2014)
BITE: Recipes for remarkable research is an edited field book capturing the research, learning and experiences of an international network of scholars studying effective and creative research environments. The book encapsulates what it is that enables remarkable research, and offers, as Professor Lizbeth Goodman says, "practical, evidence-based instantiations of ideas and innovations" as well as theoretical knowledge. It is set out as a recipe book, with supporting academic papers and case studies.; Readership: Educational Researchers and their students